Isolation, identification and genetic variation analysis of pseudorabies virus mutant strain from Chinese pig farm - Zhou, B; Wang, X; Xin, C; Lin, J; Dong, S; Wen, Y; Zhang, R; Shan, H; Zhang, Hongliang (Journal of the Hellenic Veterinary Medical Society, 2024)
ABSTRACT: Pseudorabies (PR) is an important infectious disease affecting pig farms worldwide. In this study, we reported a pseudorabies virus (PRV) isolated from a Bartha-K61-vaccinated pig farm in Linyi, Shandong Province, China. Evidence from virus isolation, electronic microscope observation，laboratory animal infection, and histopathologic examination confirmed that the etiological agent of the disease is PRV SD-2017. Sequence alignment of the gE gene indicated that it belongs to a new mutated PRV strain. The gB sequence alignment showed that compared with the Bartha and Kaplan genotype 1 strains, SD-2017 strain had a deletion of three amino acids at positions 75-78 (SPG) and an insertion of one amino acid at position 94 (G). The gC gene had 7 amino acids (A, A, A, S, T, P and A) inserted at positions 69-75 in comparison with the Bartha-K61 vaccine strain. The median lethal dose (LD50) of PRV SD-2017 strain on rabbits was 3.16×102.0TCID50/ml by Karber method. Histopathologic examinations showed that multiple lesion sites were observed in brains, lungs, livers and kidneys. PRV SD-2017 is different from other reports and should be paid more attention to avoid economic losses. Keywords: Pseudorabies virus; Sequence alignment; Amino acid mutations；Mutant strain